Dinamika Loyalitas Kerja Karyawan Pada Generasi Z - Rahayu, Thesa Fuji (CV. Green Publisher Indonesia, 2025)
This study aims to understand the dynamics of employee loyalty in Generation Z by using a phenomenological approach. Generation Z is known as a generation that is adaptive to technology, but is often considered to have low loyalty to the workplace. Seven Generation Z employees who work in the private sector were participants in this study. Data collection was carried out through in-depth interviews, then the data was validated using triangulation with significant others and analyzed thematically to find the essence of their work loyalty experience. The results of the study show that the loyalty of Generation Z employees is influenced by work comfort, positive social relationships, appreciation from superiors, and clarity of career path. Their loyalty comes in emotional, strategic, and conditional forms. The impact of loyalty is seen on performance stability, increased sense of responsibility, and work attachment. For Generation Z, loyalty is not understood as a long-term bond alone, but as an alignment between personal values, organizational goals, and meaningful work experience.